Self-perceived views on offender rehabilitation in detained adolescent boys: a qualitative analysis in the context of the good lives model - Serie, Colinda M. B.; De Ruiter, Corine; Pleysier, Stefaan; Put, Johan (Frontiers in Psychology, 2023)
An upcoming offender rehabilitation model, the Good Lives Model (GLM), proposes that effective offender rehabilitation should adopt a dual focus: reducing recidivism risk as well as enhancing the offender’s well-being. To achieve this, the GLM suggests rehabilitation should include the prosocial fulfilment of a universal set of human needs termed ‘primary goods’. A focus on primary goods attainment and well-being is hypothesized to improve treatment motivation and achieve more sustainable desistance from future offending. Although this model sounds promising, empirical evidence for these assumptions is limited, especially among youth. Twenty Flemish and Dutch detained adolescent boys (14 to 17 years old at the time of their arrest) were interviewed during their detention using a semi-structured interview. They were asked about their well-being, needs and goals during rehabilitation, their treatment motivation, and their views on recidivism and rehabilitation. The results show that a match between the boys’ well-being needs, and the treatment goals set in collaboration with the institution could improve treatment motivation and rehabilitation efforts. The boys also mentioned other factors with a positive impact on their treatment motivation: increased levels of freedom and autonomy; having a future (prosocial) perspective; investing in a therapeutic alliance; and, working on individual factors (i.e., improving coping skills, school or work skills, and relationships with prosocial friends and family). These factors closely align with working on the GLM primary goods of ‘excellence in work and play’, ‘excellence in agency’ and ‘relatedness’, which can be helpful in enhancing well-being and treatment motivation in offender rehabilitation.